Over a million students use our free study notes to help them with their homework
Use implicit differentiation on original equation- 12x + 3x(dy/dx) + 3y - 2y(dy/dx) = 0 dy/dx= -12x -3y/(3x-2y) at A, x= -5 and y= 10 therefore, dy/dx=-6/7 To find the normal of t...
This requires the chain rule and the product rule to be used to differentiate the function. The substitution u = x2 can be used to make this easier. Using this, du/dx = 2x and y = (u-5)eu<...
To find a local minimum (i.e. a point where the function changes from a negative slope into a positive slope), we first need to find all points where the slope of the function is zero. The first derivativ...
A simple way to prove this is to sub in the values that we are given. so f(x) will represent our equation x^3-3x+1 (that is f(x) = x^3-3x+1)f(-2) = -1 < 0f(-1) = 3 > 0The first thing we notice is th...
Start off with:x2+x=12Subtract 12 from both sides:x2+x-12=0Factorise:(x-3)(x+4)=0Solution is therefore:x=3 or x=-4
←
153
154
155
156
157
→
Internet Safety
Payment Security
Cyber
Essentials